Провадження з перевірки судових рішень у проекті КПК України: здобутки і прорахунки - Бобечко, Н.Р. (Альманах права, 2012)
У статті розглянуто регламентацію кримінально-процесуальної діяльності у Розділі V «Судове провадження з перегляду судових рішень» проекту КПК України. Аналізуючи відповідні положення проекту КПК України, автор подає своє бачення питань, що входять до предмета дослідження, висловлює пропозиції щодо вдосконалення законопроекту. В статье рассмотрена регламентация уголовно-процессуальной деятельности в Разделе V «Судебное производство по пересмотру судебных решений» проекта УПК Украины. Анализируя соответствующие положения проекта УПК Украины, автор приводит свое видение вопросов, входящих в предмет исследования, высказывает предложения по усовершенствованию законопроекта. The adoption of the new Draft Criminal Procedure Code of Ukraine (hereinafter — the DCPC) would represent the completion of long-term judicial reform in Ukraine. The draft Code of Ukraine has the extraordinary social and legal importance for codified legislation. The aim of the article is to analyze the regulation of criminal procedure in Section V «The proceedings for revision of judgments» of DCPC. Unlike other stages of the proceedings and the applicable criminal procedural legislation of Ukraine, the analyzed part of the criminal procedure has not undergone such radical changes. Many provisions of current Criminal Procedure Code of Ukraine dated on 1960, like: the formulation of the grounds for reviewing judgments of the Cassation Court, the contents of the proceedings in the Supreme Court of Ukraine etc., or similar by content (for example, regulation of judicial appeal decisions, determination of individuals who may file an appeal, a statement of the normative content of the grounds for modification or cancellation the judgments in appeal, etc.). DCPC took to model appeal as far as current Criminal Procedure Code of Ukraine in 1960 was mixed. The authors of DCPC filled a number of so called «pure» cassation. The novelty of the DCPC also gives to appeal or cassation court judge (the future Judge-Rapporteur) exclusive authority to verify the appellate and cassation appeal with the law for its content and form, setting the proper subject of appeal and cassation appeal, determining compliance with the terms to file an appeal and cassation, and establishing the admissibility of the facility and grounds for appeal and cassation review (Articles 398, 399, 428, 429 of DCPC). The DCPC is the subject for transformation the pre-institute of criminal proceedings of the Court of Appeal which not only renamed the «preparation for appellate review» (p. 401), but ruled out such a task as the exercise of judicial control of legality and validity of the trial court acceptance of appeals decision and related issues. The special features of the appeal proceedings at DCPC should include the ability to probe judgments and decisions of the trial court only after appeal (Part 1 of Art. 424). The positive regulatory proceedings to review judicial decisions should include: firstly, the removal of provisions for determining the date of appeal and cassation; second, to install the same for the appeal and cassation court rules that define the scope of their review of the judgment. Third, formal consolidation rules about unacceptable deterioration of the situation of the accused under appeal (Article 421 CPC Project Ukraine). Fourth, the expansion of the grounds for review the judgments by new circumstances — «the establishment of the Constitutional Court of Ukraine unconstitutionality by law, other legal acts or their separate provisions applied by the court» (p.5 Part 2 of Art. 459 DCPC). In the conceptual issues the authors of DCPC did not change the procedure of conducting court decisions. The authors of DCPC did not add anything new to the procedure of reviewing the judicial decisions and the criteria of court decisions lawfulness, and in some cases led them to a level which is very far from perfect.